Innovative Process and Structural Indicators: Actors´ Position and Technological Trajectory in Potiguar´s Network Carciniculture - Freire, Ayalla Cândido; Baldi, Mariana (Organizações & Sociedade, 2014)
Although progress has been made on the analyses of the role of social relations on economic action, little attention has been given to the innovative process as socially embedded in the Brazilian context. From this perspective, we need to analyze it as socially embedded, investigating how social relations between private and public actors interfere in the generation of innovation. For doing this we take the case of carciniculture in RN. Using the Social Network Analysis, we consider the structural indicator of network position, whose matrix of relationships between actors allows to visualize the evolutionary nature of the network structure and its implications on the innovative process. Based on semi-structured interviews, interpreted by content analysis, we describe the phenomenon in a longitudinal and inductive approach, whose cross-sectional analysis along the technological trajectory revealed more limits than opportunities for the generation of innovation, highlighting the problem of sharing information on the network.